2021
DOI: 10.30574/wjbphs.2021.5.1.0002
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant bacteria isolated from automated teller machine in metropolitan area of São Paulo, Brazil

Abstract: The aim of this study was to investigate bacterial contamination on surfaces of randomly selected Automated Teller Machine and their sensitivity to antibiotics in São Paulo city, Brazil. The swabs collected aseptically were inoculated in selective and non-selective media in triplicate and incubated at 37 °C for 24 h. After Gram staining the isolated colonies, complementary biochemical tests were applied. The antibiotic sensitivity pattern of all isolates (15 Gram-positive bacteria and 7 Gram-negative bacteria)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In Lafia, Nasarawa State, an investigation of bacterial contamination associated with ATM keypads revealed the existence of harmful microorganisms such as Salmonella sp., Bacillus sp., Pseudomonas sp., Staphylococcus aureus, Klebsiella sp., and Enterobacter sp. The findings of this study have implications for public health as ATM keypads may serve as sites for the spread of viruses [3].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In Lafia, Nasarawa State, an investigation of bacterial contamination associated with ATM keypads revealed the existence of harmful microorganisms such as Salmonella sp., Bacillus sp., Pseudomonas sp., Staphylococcus aureus, Klebsiella sp., and Enterobacter sp. The findings of this study have implications for public health as ATM keypads may serve as sites for the spread of viruses [3].…”
Section: Introductionmentioning
confidence: 83%
“…In their investigations, Barbosa et al [23], and Aquino et al [24], also identified almost the same spectrum of bacteria, but this time they linked it to multidrug resistance. The human pathogens that were found during this study are enteric bacteria, and they have been linked to nosocomial infections [25][26].…”
Section: Staphylococcus Aureus Is a Common Componentmentioning
confidence: 96%
“…This raises their potential to be vehicles for the transmission of micro-organisms, which cause infections that are difficult to treat as substantiated in numerous studies conducted in Europe, Asia and Africa. 3,[20][21][22][23][24] In Tanzania, little is known about the presence of pathogenic bacteria on ATMs surfaces, however, there is literature indicating the existence of pathogenic bacteria including ESBLs and quinolone resistance bacteria in the community. [25][26][27][28][29] This study aimed to determine the proportion of MDR Gram-negative bacteria contamination on ATMs surfaces and antimicrobial resistance patterns as well as associated factors in Dar es Salaam, Tanzania.…”
Section: Introductionmentioning
confidence: 99%